A Systematic Review of Scientific Literacy in Early Childhood Science Learning: Approaches, Methods, and Media - Rizqy Aisyah Leonia; Nelva Rolina; Eni Suyantri (Jurnal Penelitian Pendidikan IPA, 2025)
Building scientific literacy from an early age is essential for developing critical thinking skills, problem-solving abilities, and a basic understanding of scientific concepts. This article presents a systematic review of science learning strategies for young children, highlighting effective approaches, methods, and media. The study analyzes literature from various scholarly sources within a specific timeframe. The findings indicate that inquiry-based approaches, such as water and ice experiments to understand phase changes, as well as play-based and environmental exploration approaches, such as observing insects in a garden, are effective in enhancing young children's scientific literacy. Simple experimental methods, such as creating a volcanic eruption using baking soda and vinegar, and STEM-based projects help children grasp scientific concepts concretely. Learning media, including natural teaching aids (leaves and rocks for classification), interactive digital applications, and augmented reality-based educational games, have been proven to increase children's engagement. The implications of this study emphasize the importance of integrating hands-on experiences and technology in early childhood science education to create enjoyable and meaningful learning experiences. This article serves as a reference for educators and researchers in designing innovative and effective science learning strategies